Temporal shifts in gyrA mutation types and sublineage replacement in ST11 Salmonella enterica serovar Enteritidis over a decade (2014–2023): A genomic epidemiological study in Guangxi, China - Xianying Zeng; Lanqi Li; Lanxin Zhao; Jianyun Zhao; Menghan Li; Ruicheng Zheng; Mengmeng Shi; Dongmei Tan; Shaoting Li; Yang Wang; Yongning Wu; Li Bai (Food Research International, 2026)

CELF2-dependent RNA Regulation Supports Cortical Architecture and Synaptic Stability During Early Brain Development - Ishana Syed; Jing Jiang; Su-Hyuk Ko; Shaoting Chen; Zhao Zhang; Zhijie Liu; Lizhen Chen (Molecular Neurobiology, 2026)

Nano-silicon mitigates sulfamethoxazole-induced stress in wheat seedlings: Integrated transcriptomic and metabolomic analysis - Qianqian Liu; Ziting Jin; Xinyu Liao; Jie Feng; Zhiheng Li; Wenlu Zhao; Yaxin Zhu; Ran Wu; Shaoting Du; Huijun Liu (Journal of Environmental Chemical Engineering, 2025)

Cell-permeable PI3 kinase competitive peptide inhibits KIT mutant mediated tumorigenesis of gastrointestinal stromal tumor (GIST) - Zongying Jiang; Yue Guo; Jun Shi; Shaoting Zhang; Liangying Zhang; Yapeng Wang; Guofu Li; Ru Bai; Hui Zhao; Jianmin Sun (Molecular Biology Reports, 2024)

Effects of sand substrate removal on the intestinal antioxidant and metabolism in Marsupenaeus japonicus - Kuangcheng Zhao; Shaoting Jia; Junxia Wang; Xueqiong Bian; Shibo Chen; Jitao Li; Ping Liu; Jian Li; Yuefeng Cai; Xianyun Ren (Fish & Shellfish Immunology, 2024)

Changes in glacier surface temperature across the Third Pole from 2000 to 2021 - Shaoting Ren; Tandong Yao; Wei Yang; Evan S. Miles; Huabiao Zhao; Meilin Zhu; Shenghai Li (Remote Sensing of Environment, 2024)

Environmental fate of microplastics in alpine and canyon-type river-cascade reservoir systems: Large-scale investigation of the Yalong River in the eastern Qinghai-Tibet Plateau - Yixuan Liu; Shaoting Zhao; Dongzhi Wang; Shichen Wang; Xiaofan Ding; Kaiyang Han; Ruiying Wang; Yuyang Kou; Guangqian Zhou; Weibo Shen (Science of The Total Environment, 2024)

External phosphorus enhances the efficient acquisition of phosphorus by alfalfa (Medicago sativa L.) through its interaction with root morphological traits and rhizosphere carboxylates - Tengyue Du; Shaoting Zhao; Xiaoqin Zheng; Xiaofan Ding; Huan He; Gang Xie; Junhao Zhu; Yuyang Kou; Weibo Shen (Rhizosphere, 2024)

Effect of RpoS on the survival, induction, resuscitation, morphology, and gene expression of viable but non-culturable Salmonella Enteritidis in powdered infant formula - Zhuolin Ma; Weiying Xu; Shaoting Li; Siyi Chen; Yuheng Yang; Zefeng Li; Tong Xing; Zepeng Zhao; Dongping Hou; Qingqing Li; Ziying Lu; Hongmei Zhang (International Journal of Food Microbiology, 2024)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

miR-181a targets PTEN to mediate the neuronal injury caused by oxygen-glucose deprivation and reoxygenation - Shengnan Li; Peiyi Zhu; Yajun Wang; Shaoting Huang; Zhaochun Wu; Jiawen He; Xingjuan Hu; Ying Wang; Yanquan Yuan; Bin Zhao; Guoda Ma; You Li (Metabolic Brain Disease, 2023)

The effect of air exposure and re-water on gill microstructure and molecular regulation of Pacific white shrimp Penaeus vannamei - Qiong Wang; Qianqian Ge; Zhao Chen; Jiajia Wang; Shaoting Jia; Yuying He; Jitao Li; Zhiqiang Chang; Jian Li (Fish & Shellfish Immunology, 2023)

Construction of a rAAV-SaCas9 system expressing eGFP and its application to improve muscle mass - Shaoting Weng; Yitian Zhao; Changhong Yu; Xiaofan Wang; Xuehan Xiao; Liqiang Han; Kunpeng Zhang; Jiang Wang; Guoyu Yang (Biotechnology Letters, 2021)
An ideal rAAV gene editing system not only effectively edits genes at specific site, but also prevents the spread of the virus from occurring off-target or carcinogenic risks. This is important for gene editing research at specific site in vivo. We report a single rAAV containing SaCas9 and guide RNAs under the control of subtle EF1a and tRNA promoters. The capacity of rAAV was compressed, and the editing efficiency was similar to that of the classical Cas9 system in vitro and in vivo. And we inserted the sequence of the green fluorescent protein eGFP into rAAV. The number of cells infected with the rAAV and the region in which the rAAV spreads were known by the fluorescent expression of eGFP in cells. In addition, we demonstrated that myostatin gene in the thigh muscles of C57BL/10 mice was knocked out by the rAAV9-SaCas9 system to make muscle mass increased obviously. The protein eGFP into rAAV has significant implications for our indirect analysis of the editing efficiency of SaCas9 in the genome of the target tissue and reduces the harm caused by off-target editing and prevents other tissue mutations. The rAAV system has substantial potential in improving muscle mass and preventing muscle atrophy.